Application Design of Private Cloud of Enterprise Based on Water Resources Survey and Design ——A Case Study of Cloud Platform of Dongguan Water Resources Survey and Design Institute - LIANG Qian; CHEN Guotao; ZHONG Rongguang (Renmin Zhujiang)
The private cloud is good at providing services for big data inside and outside theenterprise. Taking Dongguan water resources survey and design institute as an example, thispaper studies the application of private cloud in water resources survey and design enterprisesdeeply based on the internal professional division of labor and the actual external productionservices, and proposes the application mode, architecture, service scope, data source andmanagement mode of private cloud, which provide reference for application of private cloud in similarenterprises.